KEBIJAKAN REHABILITASI TERHADAP PENYALAH GUNA NARKOTIKA PADA UNDANG – UNDANG NOMOR 35 TAHUN 2009 TENTANG NARKOTIKA - IDA BAGUS PUTU SWADHARMA DIPUTRA (Jurnal Magister Hukum Udayana (Udayana Master Law Journal), 2013)
Positive law states, drug users are criminals because it has met the qualifications in the law of narcotics, narcotic offenses such as drug abuse in the study of criminology can be classified as a crime without a victim or a victimless crime. This is because they will become dependent on illicit goods (narcotics), the way it deems appropriate to cure the addiction is to rehabilitate the victims of drug abuse For law journal writing, the writer uses normative legal research with one character is using secondary data, where the data consists of primary legal materials, legal materials and secondary legal materials tertiary. And the theoretical foundation that is used is the law, norms and theories appropriate to the problem The results reveal the writing on the rehabilitation policy on Narcotics has been strictly regulated in Chapter IX legislation, policies were aimed at drug addicts and victims of drug abuse, arguing that victims of drug abuse is a victim of crime narcotics and therefore the appropriate sanctions to be meted out to him is the rehabilitation of the victims will be able to return to society and become useful